Effects of maternal gestational diet, with or without methionine, on muscle transcriptome of Bos indicus-influenced beef calves following a vaccine-induced immunological challenge. - Elizabeth A Palmer (Public Library of Science (PLoS), 2021)
Maternal nutrition during gestation can cause epigenetic effects that translate to alterations in gene expression in offspring. This 2-year study employed RNA-sequencing technology to evaluate the pre- and post-vaccination muscle transcriptome of early-weaned Bos indicus-influenced beef calves born from dams offered different supplementation strategies from 57 ± 5 d prepartum until 17 ± 5 d postpartum. Seventy-two Brangus heifers (36 heifers/yr) were stratified by body weight and body condition score and assigned to bahiagrass pastures (3 heifers/pasture/yr). Treatments were randomly assigned to pastures and consisted of (i) no pre- or postpartum supplementation (NOSUP), (ii) pre- and postpartum supplementation of protein and energy using 7.2 kg of dry matter/heifer/wk of molasses + urea (MOL), or (iii) MOL fortified with 105 g/heifer/wk of methionine hydroxy analog (MOLMET). Calves were weaned on d 147 of the study. On d 154, 24 calves/yr (8 calves/treatment) were randomly selected and individually limit-fed a high-concentrate diet until d 201. Calves were vaccinated on d 160. Muscle biopsies were collected from the same calves (4 calves/treatment/day/yr) on d 154 (pre-vaccination) and 201 (post-vaccination) for gene expression analysis using RNA sequencing. Molasses maternal supplementation led to a downregulation of genes associated with muscle cell differentiation and development along with intracellular signaling pathways (e.g., Wnt and TGF-β signaling pathway) compared to no maternal supplementation. Maternal fortification with methionine altered functional gene-sets involved in amino acid transport and metabolism and the one-carbon cycle. In addition, muscle transcriptome was impacted by vaccination with a total of 2,396 differentially expressed genes (FDR ≤ 0.05) on d 201 vs. d 154. Genes involved in cell cycle progression, extracellular matrix, and collagen formation were upregulated after vaccination. This study demonstrated that maternal supplementation of energy and protein, with or without, methionine has long-term implications on the muscle transcriptome of offspring and potentially influence postnatal muscle development.